SOCIAL PERSONALITY DEVELOPMENT: AN EXPLORATION OF THE HUMANISTIC PSYCHOLOGY OF THE MAIN CHARACTER IN ARABIC NOVEL - khoiriyah khoiriyah; Ahmad Ali Riyadi; Tafida Yumna Annisa (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
This study aims to describe and analyze the personality of the main character in the Arabic novel Alzheimer's by Ghazi Abdurrahman Al-Ghosaibi with the psychological theory of humanism, Carl Rogers. Personality analysis is carried out based on self-concept and the process of self-actualization of the main character in the novel. This qualitative research uses descriptive analysis methods, using data and sources from the Arabic novel Alzheimer's by Ghazi Abdurrahman Al-Ghosaibi. The data collection method uses documentation by relating each find in the novel to the theory used. The data validity technique in this study uses the perseverance technique. This study concludes that the personality that appears in the main character in the novel is influenced by the self-concept formed before and after suffering from Alzheimer's and the nature created based on the process of self-actualization. From these two concepts, the main character's personality varies depending on the influence caused by the idea